WHV AUSTRALIA AND POLICY IMPLICATIONS FOR INDONESIAN PARTICIPANTS - Irsyaad Suharyadi; Arie Fitria (Jurnal Kebijakan Publik, 2026)
The Australian Working Holiday Visa (WHV) is a temporary migration policy that has become one of the most favored international migration schemes among Indonesia's young generation. This is in line with the increase in the WHV participant quota, which will reach 5,500 people by 2025. Although introduced as a "work and holiday" program, most WHV participants work in agriculture, hospitality, and several other high-risk sectors. This study aims to analyze the vulnerability of Indonesian WHV participants in Australia by conducting a case study over the period 2023-2025. This study employs qualitative methods by analyzing academic literature, official reports, and documented cases related to the vulnerabilities experienced by Indonesian WHV participants. The results show that the vulnerability of WHV participants stems from several structural weaknesses in the governance of the WHV policy. Throughout 2023-2025, there were seven published traffic accidents resulting in 10 fatalities and 5 injuries, two published cases of work accidents, and one published fraud/scam that harmed Indonesian WHV participants. Analysis using Neoliberal Institutionalism theory indicates asymmetric gains where Australia benefits more than Indonesia. Meanwhile, from a Temporary Migrant Labour perspective, it is known that WHV participants are in a state of unfree labor due to the threat of exploitation in the work environment, unfavorable immigration policies, and economic conditions that drive them to repeat migration. This research encourages improvements in Australia's WHV cooperation with Indonesia, such as providing pre-departure outreach, participant monitoring, legal protection, and effective reporting mechanisms to minimize risks for WHV participants and enhance cooperation between Indonesia and Australia.